Pedagogia dos corpos vivos: relações entre educação popular, agroecologia e camponeses experientes de diferentes gerações - Rodrigues, Tessy Priscila Pavan de Paula (2021)
This research seek to investigate the peasant intergenerational relations from distinct generations, that have some youth individuals grounded and degreed on the “Course on Agrarian Residence” (RAJ-PB), understanding this relation like genuine process of “Popular Education”. Those peasants take the Agroecology like a synthesis-force that, linked on a societal project, invite us to reconfigure the metabolism between nature and society. Getting Start from the question “Which educational process inspired the new generations in the trail of agroecology”?, this thesis is organized in four central divisions chapters. The first chapter presents roots and research paths, that have methodological procedures anchored on the Participative Research strategies, with ethnography appointments. The methodological tools utilized were: bibliographic revision, archive researches and documents resulted from the “Course on Agrarian Residence” (RAJ-PB) and produced by youth degreed from that classes, revisiting the field annotations e and semi-structured interviews. The central conceptual categories of Work, “Popular Education” and Agroecology, has been related and integrated on the Second Chapter, where are the bases and connections between its-self. This relationship is considered on its potential confronting lhe micropolíticas paradigma. The relato betem lhe South passante and. lhe olá passantes generativos are approaches no lhe Tiro Charter, cheire lhe ressarce subjects are revealed like experienced peasant in the Agroecology trail. Historical elements about the life production territories and the meaning objectives dreamed by those individuals, and their interfaces with collective projects, appear like central points to reconstruct our biocultural memory. The agroecology meaning to the research subjects worked on the fourth chapter indicates commons significations, that makes the peasants, their ancestral and the land as the most important agroecology meaning constructors. Concluding that the intergeneration relationship between experienced peasants, through by distinct educative and formative agents in the trails of agroecology construct a “Pedagogy of living bodies” (Pedagogia dos Corpos Vivos) based on the circular knowledge, by the time that keep alive seems to be epical question and urgent human challenge, as the same time that life disdain get over as hegemonic systematical practical in the brazillian actualities.